The Papers of John Marshall : Vol. VIII: Correspondence, Papers, and Selected Judicial Opinions, March 1814-December 1819 - Marshall, John, 1755-1835 (Book collections on Project MUSE., 1974)
At the close of 1830 John Marshall (1755-1835) had passed his seventy-fifth year and completed his third decade as chief justice of the United States. The preceding four years had been among the busiest of his long and active life. Between April 1827 and December 1830, Chief Justice Marshall delivered numerous circuit court opinions as well as six Supreme Court opinions that addressed issues of constitutional law. His travels on judicial business regularly took him from his Richmond home to Washington and to Raleigh. Marshall attended a convention on internal improvements in Charlottesville in July 1828, and he served as a delegate to the Virginia Constitutional Convention in Richmond from October 1829 to mid-January 1830. Continuing the acclaimed annotated edition of the papers of John Marshall, this volume sheds light not only on the great statesman and jurist's life and thought but on the evolution of American jurisprudence as well. -- Publisher description.